Efektifitas Pembelajaran Daring Selama Pandemi Covid 19, Dampaknya Terhadap Kemandirian Belajar Dan Motivasi Belajar Mahasiswa Universitas Serang Raya Banten - Hany Azza Umama; Nurhayani Nurhayani (Sains: Jurnal Manajemen dan Bisnis, 2021)
During the Covid-19 Pandemic, the Ministry of Education and Culture has ordered to hold lectures or online learning. These changes not only have an impact on educational institutions but also have an impact on students to quickly adapt to the demands of the environment. In this online learning application, of course it makes it natural that there are pros and contra related to the effectiveness of online learning. In addition, there are differences in the results of research on the influence of online learning on independent learning and learning motivation is also contradictory, based on this phenomenon it is very important to research. The purpose of this study was to determine the effectiveness of online learning at the Serang Raya University of Banten, to determine the impact of effectiveness on independent learning and student learning motivation. This study used a sample of 175 students at the Serang Raya University of Banten who where given randomly. Simple linear regression analysis was used to analyze the relationship between each variable in the study. This research will produce the effectiveness of online learning, its impact on motivation, its impact on independence, reduce public anxiety about online learning, and provide a direction of support for previous research that is contradictory.